2021
DOI: 10.1111/jvim.16186
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a continuous glucose monitoring system in neonatal foals

Abstract: Background: Monitoring blood glucose concentrations is common in critically ill neonatal foals, especially septic foals and those receiving naso-esophageal feedings or IV parenteral nutrition. Glucose typically is measured using a point-of-care (POC) glucometer but requires repeated restraint and blood collections, which may cause irritation at venipuncture sites and increased demands on nursing staff. Continuous glucose monitoring systems (CGMS) may provide an accurate alternative for monitoring blood glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, concerns persist over measurement accuracy and comparability (i.e., to traditional lab assays) when using POC devices, especially in wild animals, where this has not been frequently investigated. Some studies using POC glucometers found accurate levels of blood glucose in foals (Wong et al, 2021), dogs (Lane et al, 2015), and birds (McGraw et al, 2020; Morales et al, 2020), but in house sparrows ( Passer domesticus ) researchers found only moderate repeatability of glucose, ketone, and uric acid compared with lab assays (Beattie et al, 2022). There is also the growing need to understand the extent to which these hematological measurements yield information about separate or linked physiological processes (i.e., are concentrations of different blood nutrients intercorrelated?)…”
Section: Introductionmentioning
confidence: 99%
“…However, concerns persist over measurement accuracy and comparability (i.e., to traditional lab assays) when using POC devices, especially in wild animals, where this has not been frequently investigated. Some studies using POC glucometers found accurate levels of blood glucose in foals (Wong et al, 2021), dogs (Lane et al, 2015), and birds (McGraw et al, 2020; Morales et al, 2020), but in house sparrows ( Passer domesticus ) researchers found only moderate repeatability of glucose, ketone, and uric acid compared with lab assays (Beattie et al, 2022). There is also the growing need to understand the extent to which these hematological measurements yield information about separate or linked physiological processes (i.e., are concentrations of different blood nutrients intercorrelated?)…”
Section: Introductionmentioning
confidence: 99%